The French economy in the twentieth century - Dormois, Jean-Pierre (New studies in economic and social history ;, 2004)
"This new textbook examines the spectacular transformation that the French economy has undergone over the past century. Jean-Pierre Dormois offers a general introduction to the major trends as well as recent transformations of French society, and an overview of modern economic development. He tackles the key themes associated with the French 'path of economic development'--Malthusianism, exceptionalism and Colbertism. Other chapters address standard economic issues relating to the role of human capital formation, economic institutions and openness to the rest of the world. The author examines and interprets trends and features of the period as a whole, and sets them in a wider European framework. This book offers students a helpful and concise summary of recent research, and presents a uniquely synthetic view of the French economy in the twentieth century. It will have broad appeal for students and teachers of French and of European history and economics."--Publisher description